2008
DOI: 10.1111/j.1530-0277.2008.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Study of FASD in a Sample of American Indian Children: Processing Simple Versus Complex Information

Abstract: Background-While a large body of literature exists on cognitive functioning in alcoholexposed children, it is unclear if there is a signature neuropsychological profile in children with Fetal Alcohol Spectrum Disorders (FASD). This study assesses cognitive functioning in children with FASD from several American Indian reservations in the Northern Plains States, and it applies a hierarchical model of simple versus complex information processing to further examine cognitive function. We hypothesized that complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 47 publications
2
60
0
1
Order By: Relevance
“…Additionally, many school-age children struggle recalling instructions provided orally and following them (Carpenter, 2011). Research also indicates that individuals with FASD experience difficulties meeting learning and behavioral expectations when there are changes in the routine and variations in the tasks presented (Aragon et al, 2008b;Hamilton, Kodituwakku, Sutherland, & Savage, 2003;Kodituwakku et al, 2001). Teachers have reported success through the use of consistent routines, visual schedules, pairing short concrete directions with visual cues, and repeating instructions and rules as needed (Carpenter, 2011).…”
Section: Social Emotional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many school-age children struggle recalling instructions provided orally and following them (Carpenter, 2011). Research also indicates that individuals with FASD experience difficulties meeting learning and behavioral expectations when there are changes in the routine and variations in the tasks presented (Aragon et al, 2008b;Hamilton, Kodituwakku, Sutherland, & Savage, 2003;Kodituwakku et al, 2001). Teachers have reported success through the use of consistent routines, visual schedules, pairing short concrete directions with visual cues, and repeating instructions and rules as needed (Carpenter, 2011).…”
Section: Social Emotional Developmentmentioning
confidence: 99%
“…This grouping may help students with FASD form connections between the words and their meanings, and may make retrieval of the information easier when prompted with the clustering category. Although children with FASD learned less verbal information when presented in a standard format, when the information was presented using semantic clustering, there were no differences exhibited in the learning or memory between children with and without FASD (Aragon et al, 2008b;Kodituwakku et al, 2006;Roebuck-Spencer & Mattson, 2004).…”
Section: Cognitive Developmentmentioning
confidence: 99%
“…milder physical signs and intellectual performance within borderline or slightly lower normality parameters [16][17][18][35][36][37] . This aspect was presented in a 1981 publication 18 .…”
mentioning
confidence: 99%
“…As for the most compromised spoken language components, we note that the majority of studies mentioned the semantic 18,[21][22][23]25,27,28,[34][35][36] , syntatic 16,18,19,20,25,34 and pragmatic 17,18,27,28 components.…”
mentioning
confidence: 99%
“…It is noteworthy that FAS is considered to be one of the major identifiable and non-genetic causes of intellectual disability. 3 Furthermore, some studies concluded that the intellectual functioning in individuals exposed to alcohol during pregnancy is of average level, 4,5 while others found that most individuals with FASD are not intellectually impaired 3 . No statistically significant effect on intelligence of low to moderate alcohol consumption and episode of binge drinking during gestation was found in a series of studies of a Danish cohort.…”
mentioning
confidence: 99%